Reasons for variance of year-class strength for the Amur pink salmon Oncorhynchus gorbuscha (Walbaum) - V. I. Ostrovsky (Известия ТИНРО, 2023)
The Amur pink salmon catches dependence on the yields landed 2 years before is investigated for 1980–2018. The relationship could be approximated well by a linear regression with deviations explained almost completely by variations of precipitation and air temperature in autumn-winter of the year of spawning. There is shown that the forecast of the pink salmon annual catch could not be realized in 2018 because of the extremely low air temperature and lack of precipitation in 2016 (the lowest values for the 40-year period). Reasons for the strength alternation between the even and odd year-classes of pink salmon are discussed.